The effectiveness of tobacco control television advertisements in increasing the prevalence of smoke-free homes - Lewis, Sarah; Sims, Michelle; Richardson, Sol; Langley, Tessa; Szatkowski, Lisa; McNeill, Ann; Gilmore, Anna B. (BioMed Central, 2015)
BACKGROUND: There is considerable evidence that tobacco control mass media campaigns can change smoking behaviour. In the UK, campaigns over the last decade have contributed to declines in smoking prevalence and been associated with falls in cigarette consumption among continuing smokers. However, it is less evident whether such campaigns can also play a role in changing smokers’ behaviour in relation to protecting others from the harmful effects of their smoking in the home. We investigated whether exposure to English televised tobacco control campaigns, and specifically campaigns targeting second hand smoking, is associated with smokers having a smoke-free home.